1977
DOI: 10.1017/s0094837300005121
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive radiation of the comatulid crinoids

Abstract: Modern crinoids are dominated by the comatulids (unstalked forms) which range from the intertidal to abyssal depths. Modern stalked crinoids are restricted to depths greater than about 100 m. In the geologic past some stalked crinoids lived at depths of a few tens of meters or less in reef and bank environments. The primary vehicles postulated for the post-Triassic radiation of comatulids are lack of permanent fixation to the substratum and the capacity for mobility. Development of complex muscular articulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
134
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(137 citation statements)
references
References 10 publications
3
134
0
Order By: Relevance
“…For example, it comes as a surprise to many that some modern stalked crinoids may crawl with their arms (Baumiller and Messing 2007), and the stalkless comatulids can use the same structures for walking or swimming (Meyer and Macurda 1977). They are thus benthic, but certainly not sessile.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it comes as a surprise to many that some modern stalked crinoids may crawl with their arms (Baumiller and Messing 2007), and the stalkless comatulids can use the same structures for walking or swimming (Meyer and Macurda 1977). They are thus benthic, but certainly not sessile.…”
Section: Introductionmentioning
confidence: 99%
“…Although predation by fish on crinoids and its evolutionary consequences have received the most attention (21)(22)(23)(24)(25)(26)(27), sparse data indicated that crinoids may be the prey of benthic invertebrates (28), most notably sea urchins (17-19, 29, 30). Recently it has been shown that during the Triassic, the radiation of cidaroid sea urchins capable of handling the crinoid skeleton coincided with high frequency of bite marks on crinoids likely produced by the jaw apparatus of these sea urchins (18).…”
mentioning
confidence: 99%
“…The bite traces we report were culled from among other traces on the basis of their similarity to traces found on crinoid skeletal elements retrieved from the guts and feces of extant cidaroids (17,18). Furthermore, we collected data for stalk fragments only, as stalks are most likely to be bitten by benthic organisms, such as sea urchins, rather than fish, which have been shown to focus on crinoid arms and cups (21)(22)(23)(24)(25). The repeated co-occurrence of sea urchins at the localities from which crinoids with bite marks were recovered is also consistent with this interpretation.…”
mentioning
confidence: 99%
“…2B and Table S2). Considering the rarity of fossil crinoids with preservation of organic pigments and the poor fossil record of intact Cenozoic crinoids (2,3), the analytical data of fossil and extant crinoids strongly suggest that hypericinoids were common crinoidal pigments throughout the Mesozoic and Cenozoic, presumably with a monophyletic origin within the ancestral Articulata (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…Following the end-Permian mass extinction, which almost led to the disappearance of the Crinoidea, the post-Paleozoic crinoids, all grouped in the subclass Articulata (2), underwent a major evolutionary radiation and diversification that led to the development of free-living crinoids and to the offshore displacement of stalked crinoids (2,3).…”
mentioning
confidence: 99%